PENGELOLAAN SAMPAH ANORGANIK MENJADI ANEKA KREASI DAUR ULANG BAGI ANAK REMAJA (PAR) DAN PEMUDA (PAM) JEMAAT GKI SILOAM WAENA, KOTA JAYAPURA - Euniche R.P.F. Ramandey; Evie L. Warikar (LPPM Uncen, 2021)
Garbage is one of the serious environmental problems faced by developed and developing countries. The objectives of implementing community service activities are: (1) increase the knowledge of teenagers and the youths members of GKI Siloam Waena church, about waste management through the introduction and practice of inorganic waste management directly into various recycled creations, and (2) increase the awareness of teenagers and the youths members of GKI Siloam church, Waena about waste management by empowering them in managing inorganic waste into various recycled creations. Lecture and demonstration methods used in this activity. The steps are as follows: (1) lectures to deliver material about waste, types of waste, sources of waste, waste management and 3R (reduce, reuse, recycle), and inorganic waste management into various recycled creations, (2) followed by questions and answers, (3) a demonstration of the procedures or techniques for making preparations from inorganic waste by showing and using supporting tools to facilitate training participants in working, and (4) the practice of making various recycled creations. The overall activity has been successful and has been going well.Keywords: : environmental, management, inorganic waste, jayapura, 3R